Validating student satisfaction related to persistence, academic performance, retention and career advancement within ODL perspectives - Maximus Gorky Sembiring (Open Praxis, 2015)
Student satisfaction associated with persistence, academic performance, retention, and its relations to career advancement were examined. It was aimed at measuring service quality (Servqual) dimensions as a foundation of satisfaction and how, in what comportments, they were interrelated. The study was conducted under explanatory-design. Data was collected proportionally and purposively followed by congregating them through unified interviews. Population was 1,814 Universitas Terbuka students domiciled overseas; 350 questionnaires were dispersed, 169 completed. Satisfaction was assessed by examining Servqual dimensions. Importance-performance analysis (IPA) and customer-satisfaction index (CSI) were applied to measure satisfaction and the level of its importance. Structural equation model (SEM) was then employed to examine influencing variables. Nine hypotheses developed were all validated by the analysis. Responsiveness, assurance, tangible, reliability, and empathy were in harmony to satisfaction. Career advancement, retention, academic performance, and persistence were influenced by satisfaction. Qualitative inquiry implemented afterwards was basically coherent with the quantitative findings.